General Practitioners’ Experiences of Clinical Consultations With Refugees Suffering From Mental Health Problems - Harris, Samantha Marie; Binder, Per-Einar; Sandal, Gro Mjeldheim (Frontiers in Psychology, 2020)
Refugees suffer from higher rates of certain mental health problems than non-refugee migrants and the native population of their host country. General practitioners (GPs) in Norway and many other European countries are the first contact person for settled refugees in need of non-emergency medical support. This includes psychiatric support, although GPs are not typically specialists in psychiatry. The aim of this study is to investigate how GPs experience working with refugees suffering from mental health problems, with a specific focus on perceived challenges and facilitators. We conducted semi-structured interviews with 15 GPs working in Norway (7 females). Participants ages ranged from 29-67 (M = 41.7 years, SD = 11.1) with work experience ranging from 2-39 years (M = 13.6 years, SD = 12.1). Interviews were analysed thematically using the qualitative data analysis computer software package NVivo 12. The main challenges presented by GPs relate to language barriers, mismatched expectations, different understandings of health and illness, and the GP feeling unprepared to work with this patient group. The main facilitating themes related to establishing trust and finding the work meaningful. The themes presented in this study highlight areas of interest for future research, and should inform training programs to improve health care for both clinicians and refugee patients.